Honey Bees (Hymenoptera: Apidae) Decrease Foraging But Not Recruitment After Neonicotinoid Exposure. Issue 1 (7th February 2022) - Ohlinger, Bradley D; Schürch, Roger; Durzi, Sharif; Kietzman, Parry M; Silliman, Mary R; Couvillon, Margaret J
Abstract: Honey bees (Linnaeus, Hymenoptera: Apidae) are widely used as commercial pollinators and commonly forage in agricultural and urban landscapes containing neonicotinoid-treated plants. Previous research has demonstrated that honey bees display adverse behavioral and cognitive effects after treatment with sublethal doses of neonicotinoids. In laboratory studies, honey bees simultaneously increase their proportional intake of neonicotinoid-treated solutions and decrease their total solution consumption to some concentrations of certain neonicotinoids. These findings suggest that neonicotinoids might elicit a suboptimal response in honey bees, in which they forage preferentially on foods containing pesticides, effectively increasing their exposure, while also decreasing their total food intake; however, behavioral responses in semifield and field conditions are less understood. Here we conducted a feeder experiment with freely flying bees to determine the effects of a sublethal, field-realistic concentration of imidacloprid (IMD) on the foraging and recruitment behaviors of honey bees visiting either a control feeder containing a sucrose solution or a treatment feeder containing the same sucrose solution with IMD. We report that IMD-treated honey bees foraged less frequently (–28%) and persistently (–66%) than control foragers. Recruitment behaviors (dance frequency and dance propensity) also decreased with IMD, but nonsignificantly. Our results suggest that neonicotinoids inhibit honey bee foraging, which could potentially decrease food intake and adversely affect colony health.